2017
DOI: 10.1111/jph.12564
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pear Fruit Cuticular Wax and Surface Hydrophobicity in Regulating the Prepenetration Phase of Alternaria alternata Infection

Abstract: The role of cuticular wax and the surface hydrophobicity of the fruit of the ‘Zaosu’ pear (Pyrus bretschneideri Rehd) in regulating the prepenetration phase of Alternaria alternata infection were analysed in vivo and in vitro. Results showed that cuticular wax on an intact fruit surface, as well as wax extracts mounted on silanized glass slides or onion epidermis, favoured the formation of short, differentiated germ tubes and large numbers of appressoria (APP) or infected hyphae (IH). Dewaxed fruits or no wax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 47 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…In A. brassicicola , it is thought that conidial lipase that interacts with leaf waxes plays the main role in adhesion of conidia to the plant surface, despite the leaf surface hydrophobicity (Berto et al ., ). Intact cuticular waxes and surface hydrophobicity favoured formation of short germ tubes by A. alternata on pear fruits (Tang et al ., ). In the present investigation, production of mucilage by A. brassicicola conidia, which may adhere them to the host surface, was observed.…”
Section: Discussionmentioning
confidence: 97%
“…In A. brassicicola , it is thought that conidial lipase that interacts with leaf waxes plays the main role in adhesion of conidia to the plant surface, despite the leaf surface hydrophobicity (Berto et al ., ). Intact cuticular waxes and surface hydrophobicity favoured formation of short germ tubes by A. alternata on pear fruits (Tang et al ., ). In the present investigation, production of mucilage by A. brassicicola conidia, which may adhere them to the host surface, was observed.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, fatty acids were shown to be major components of epicuticular wax. Tang et al [24] also reported that high surface hydrophobicity resulting from cuticular wax of pear also stimulated infection structure formation of Alternaria alternata.…”
Section: Effect Of Different Cuticle Extracts On Mycelium Growth and mentioning
confidence: 94%
“…Hordei germination was more rapid and greater on the surfaces of intact than dewaxed barley [23]. Tang et al [24] observed that the chemical composition and hydrophobicity of pear fruit cuticular wax are essential in facilitating fungal invasion by regulating the growth and differentiation of Alternaria alternata during the prepenetration phase. Several other ubiquitous very-long-chain aldehyde wax constituents are capable of effectively stimulating Bluemeria graminis prepenetration processes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that PLC regulates the morphogenesis of pathogenic fungi. Our previous studies revealed a positive correlation between pear cuticular wax hydrophobicity and appressorium formation in A. alternata (Tang et al, 2017). Whether PLC-mediated Ca 2+ signaling involves this induction process requires further elucidation.…”
Section: Introductionmentioning
confidence: 89%
“…Other plant pathogenic fungi recognize primary alcohols to regulate infection related morphogenesis (Liu et al, 2011). Our previous study showed that the chemical composition and hydrophobicity of pear fruit cuticular wax is essential for fungal invasion through its regulation of the growth and differentiation of A. alternata during the pre-penetration phase (Tang et al, 2017). This highlights the role of hydrophobicity and wax as epidermal signals in pathogen-plant interactions.…”
Section: Introductionmentioning
confidence: 97%